Overview of CUDA - Petrov, Georgi (Yearbook Telecommunications, 2015)
This publication is an overview of CUDA technology, and more specifically how CUDA allocates memory card memory resources, how CUDA allocates a computing task to computing clusters and separate computing processes. The work presents a general idea of the possibilities of the technology and its possible development in the near future.